Organization of health services attention to emergencies: narrative review. - Pelegrini, Alisia Helena Weis; Santos, José Luís Guedes dos; Marques, Giselda Quintana; Ciconet, Rosane Mortari; Lima, Maria Alice Dias da Silva (Online Brazilian Journal of Nursing, 2010)
<!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; span.longtext mso-style-name:long_text; mso-style-unhide:no; span.shorttext mso-style-name:short_text; mso-style-unhide:no; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page WordSection1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –> The attention to emergency is a complex matter and symbolic in the implementation of the Brazilian National Health Care System – [SUS-Sistema Único de Saúde]. This paper aims to present a review on the organization of health services for emergency attention in Brazil, considering the presuppositions of the National Urgent Care Policy and SUS. This is a review of the narrative kind, in databases BVS and SciELO between 1999 and 2009 that totalized 12 productions. Despite advances in the policy guidelines’ urgent care, the organization and structuring of services has presented fragilities and contradictions regarding the concept that all patients will be guaranteed the host on a network of care in a regionalized, hierarchical and regulated in accordance with technological complexity. This scenario creates trouble and problems, both for the services and professionals and users, who suffer, respectively due to the overload of work and the fact of not having their health needs fulfilled. The study signals some critical nodes that need to be discussed and implemented by the health and nursing team for the effectiveness of policies to emergency attention in the health services.